Outdoor activity lab : exciting STEM projects for budding scientists - Challoner, Jack (DK Publishing, a division of Penguin Random House, 2025)
"Dive into science with these fun outdoor experiments for children to do in their own surroundings.. Outdoor Activity Lab contains 25 amazing projects to inspire young scientists and outdoor enthusiasts, taking 9-12 year olds out of the house on a journey to better understand their world. Great photography, clear step-by-step instructions and attention to detail will make young scientists excited from the get-go. There is a clear 'How it works' explanation for each project, revealing the fascinating science behind it, along with real-world examples that show everyday science in action... This book is perfect for every young scientist curious about the world. Using easy-to-find household items, you can make giant bubbles to reveal how surface tension works, construct a water rocket and blast it skyward to learn about Newton's law of physics, discover how mushrooms grow by cultivating mycelium, and make your own barometer to measure atmospheric pressure ... and much more!"--Amazon.com.